2014
DOI: 10.1007/s00192-014-2606-4
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized trial of levator injections versus physical therapy for treatment of pelvic floor myalgia and sexual pain

Abstract: Vaginal myalgia and sex-related pain improved with pelvic floor PT and LTPI. Time-to-effect improvement and significance of therapy are dependent on treatment type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…70 In a small study of 29 patients, greater than 50% improvement in pain scores was observed with physical therapy in 59% of patients and with levator-directed trigger-point injections in 58% of patients. 71 The high prevalence and severity of psychosocial issues in patients with urologic chronic pain syndromes 54 underscores the need for appropriate pharmacotherapy, counseling, and/or cognitive-behavioral therapy. These are often integrated in multidisciplinary programs that incorporate physical therapy, particularly for patients whose symptoms are refractory to other approaches.…”
Section: Methodsmentioning
confidence: 99%
“…70 In a small study of 29 patients, greater than 50% improvement in pain scores was observed with physical therapy in 59% of patients and with levator-directed trigger-point injections in 58% of patients. 71 The high prevalence and severity of psychosocial issues in patients with urologic chronic pain syndromes 54 underscores the need for appropriate pharmacotherapy, counseling, and/or cognitive-behavioral therapy. These are often integrated in multidisciplinary programs that incorporate physical therapy, particularly for patients whose symptoms are refractory to other approaches.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2014 study by Zoorob et al, two groups of women reporting dyspareunia were treated with either pelvic floor PT or levator-directed trigger-point injections. Results from this study demonstrated improvement in both groups, however the group receiving PT demonstrated a greater overall improvement in sexual function based on sexual function scores [12]. In addition to decreasing pain with intercourse, some studies have shown that pelvic floor physical therapy intervention can actually help increase sexual pleasure [13,14].…”
Section: Management Of Types Of Sexual Dysfunction Through Pelvic Flomentioning
confidence: 82%
“…A small study for women with pelvic floor myalgia showed reduction of pain with PFPT. 11 Another study showed that PFPT is beneficial in women with painful bladder syndrome and pelvic floor tenderness. 12 PFPT appears most beneficial for patients with pelvic floor dysfunction and/or myofascial pain components.…”
Section: Pelvic Floor Physical Therapymentioning
confidence: 99%